2018
DOI: 10.1101/323253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Ca2+-regulated deAMPylation switch in human and bacterial FIC proteins

Abstract: words) 21Significance statement (120 words) 44 45 Many FIC proteins regulate target proteins by addition of AMP, a reaction coined 46AMPylation. In a large FIC proteins subgroup, AMPylation is autoinhibited by a conserved 47 57 58In less than a decade, FIC proteins have emerged as a large family of enzymes controling the 59 activity of target proteins by post-translationally modifying them with phosphate-containing 60 compounds (reviewed in (1, 2 , 3 , 4 )). These proteins are characterized by the presence of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Moreover, in vitro modification of BiP by purified FICD requires mutation of Glu234, suggesting that an AMPylation repressed state is favoured by wild‐type FICD. Remarkably, the Fic domain of FICD is also responsible for BiP deAMPylation: an activity that depends on Glu234 (Casey et al , ; Preissler et al , ) and magnesium (Veyron et al , ). These findings point to deAMPylation as the default activity of the bifunctional enzyme and implicate Glu234 in a functional switch between the two antagonistic activities of the Fic active site.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in vitro modification of BiP by purified FICD requires mutation of Glu234, suggesting that an AMPylation repressed state is favoured by wild‐type FICD. Remarkably, the Fic domain of FICD is also responsible for BiP deAMPylation: an activity that depends on Glu234 (Casey et al , ; Preissler et al , ) and magnesium (Veyron et al , ). These findings point to deAMPylation as the default activity of the bifunctional enzyme and implicate Glu234 in a functional switch between the two antagonistic activities of the Fic active site.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing this ratio or removing Mg 2+ completely from the reaction mixture decreases the deAMPylation efficiency of WT HYPE. Conversely, WT HYPE efficiently catalysed BiP deAMPylation in the presence of only Mg 2+ [47]. This observation, coupled with similar results observed for the bifunctional Enterococcus faecalis Fic (EfFic), led the authors to propose a divalent metal ion differential as an alternative (or additional) mode of regulation for the displacement of Glu234 (inherent conformational flexibility) [47].…”
Section: Eukaryotic Ampylasesmentioning
confidence: 78%
“…Together, this data suggests that monomeric HYPE mutants possess enhanced AMPylation function, and a slightly but significantly repressed deAMPylase function [85]. Recent work by Veyron et al has shown that the WT HYPE-mediated BiP deAMPylation can be fine-tuned by modulating the Ca 2+ /Mg 2+ ratio in vitro [47]. Increasing this ratio or removing Mg 2+ completely from the reaction mixture decreases the deAMPylation efficiency of WT HYPE.…”
Section: Eukaryotic Ampylasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the disruption of dimerization by an I271D mutation led to increased AMPylation activity in vitro, the deAMPylation activity in vivo was retained. Next, in vivo studies showed that human FICD deAMPylation activity was fully inhibited by the presence of Ca 2+ ions (Veyron et al, 2019). In comparison, Mg 2+ ions had no impact on FICD deAMPylation catalysis.…”
Section: Regulation Of Ficd Activitymentioning
confidence: 97%